Body appreciation and attitudes toward menstruation. (January 2015) - Chrisler, Joan C.; Marván, Maria Luisa; Gorman, Jennifer A.; Rossini, Meghan
Highlights: We examine body appreciation and its connection to attitudes toward menstruation. We examine both variables in connection with desire to suppress menstrual cycles. Results may be useful in designing interventions to increase comfort with menses. Abstract: Menstruation is an important function of the female body, yet it has rarely been included in research on body image. As women's attitudes toward menstruation are so often negative, this study was designed to examine whether women with positive body image would have more positive attitudes toward menstruation. Seventy-two American women, ages 18–45 years, were recruited online to complete the Body Appreciation Scale (Avalos et al., 2005 ) and the Beliefs about and Attitudes toward Menstruation Scale (Marván et al., 2006 ) and to answer some questions about their interest in menstrual suppression. Linear regressions showed that higher scores on body appreciation predicted more positive attitudes toward and beliefs about menstruation, but were not related to interest in menstrual suppression. Our findings may be useful in designing interventions to increase women's comfort with their bodies and bodily functions.